Color box with emulation of the visible spectrum to approach concepts about electromagnetic waves in elementary school (Research, Society and Development, 2022)
Teaching physical concepts addressing electromagnetic waves is one of the significant challenges for teachers of Natural Sciences in elementary school since these teachers are usually graduated in Biological Sciences. Therefore, the objective of this work is to present an improvement of the educational object known as color box, in which the light source can emulate the entire visible electromagnetic spectrum as a function of the wavelength. It is expected that, with the use of this educational object, the elementary school student can perceive that the visible electromagnetic spectrum is continuous and that each wavelength is associated with a color in this spectrum. The color box was built using a microcontroller and low-cost electronic components. The proposed apparatus was able to emulate the visible electromagnetic spectrum (from 400 nm to 700 nm), which makes it innovative compared to the color boxes already reported in the literature. Furthermore, the use of the educational object allows the proposition of didactic activities approaching the concepts of electromagnetic waves and studying patterns of absorption and reflection of these waves by objects of different colors.